Solitary wave and periodic wave solutions for a class of singular p-laplacian systems with impulsive effects - Kong, Fanchao; Luo, Zhiguo; Qiu, Hongjun (Mathematical Modelling and Analysis, 2018)
This work deals with the existence of periodic wave solutions and nonexistence of solitary wave solutions for a class of second-order singular p-Laplacian systems with impulsive effects. A su_cient criterion for the solutions of the considered system is provided via an innovative method of the mountain pass theorem and an approximation technique. Some corresponding results in the literature can be enriched and extended.